2011
DOI: 10.3109/0886022x.2011.618972
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of Rocuronium-Induced Neuromuscular Block with Sugammadex and Resulting Histopathological Effects in Rat Kidneys

Abstract: Background: This study investigated the effect of injection of rocuronium or sugammadex alone and rocuronium + sugammadex on urea, creatinine, electrolyte levels, and histopathological findings in rats. Methods: Thirty-six SpragueDawley male rats were divided to receive intravenously 16 or 96 mg/kg sugammadex, 1 mg/kg rocuronium, 1 mg/kg rocuronium + 16 mg/kg sugammadex, or 1 mg/kg rocuronium + 96 mg/kg sugammadex. The control group received an equal volume of physiological serum. Rats receiving rocuronium wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 15 publications
(18 reference statements)
1
28
0
1
Order By: Relevance
“…So we can conclude that it was not the dose of 16 mg/kg of sugammadex, rather it was that of 96 mg/kg that resulted in signifi cant renal tissue damage in diabetic rats. Bostan et al (18) showed similar fi ndings in non-diabetic rats treated with 96 mg/kg sugammadex and concluded that elongated exposure of renal tissue to sugammadex-rocuronium complex might result in such pathologic changes. In contrast to histopathological fi ndings they could fi nd no abnormalities in blood urea and creatinine levels.…”
Section: Sugammadex and Postoperative Renal Adverse Eventsmentioning
confidence: 72%
See 3 more Smart Citations
“…So we can conclude that it was not the dose of 16 mg/kg of sugammadex, rather it was that of 96 mg/kg that resulted in signifi cant renal tissue damage in diabetic rats. Bostan et al (18) showed similar fi ndings in non-diabetic rats treated with 96 mg/kg sugammadex and concluded that elongated exposure of renal tissue to sugammadex-rocuronium complex might result in such pathologic changes. In contrast to histopathological fi ndings they could fi nd no abnormalities in blood urea and creatinine levels.…”
Section: Sugammadex and Postoperative Renal Adverse Eventsmentioning
confidence: 72%
“…The rats were classifi ed as diabetic if their fasting blood glucose (FBG) levels exceeded 250 mg/dl, and only the animals with FBG levels > 250 mg/dl were included in the diabetic groups. The rats were kept alive for four weeks after streptozotocin injection to allow the development of chronic diabetes (18).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…After 24 hours, the neurological condition of the rats was assessed with a scoring system [9,10]. The sugammadex doses were determined according to doses used in previous experimental studies [11–14].…”
Section: Methodsmentioning
confidence: 99%